The right of access to justice of accused persons in criminal procedure law of Vietnam - Hoang, Thi Bich Ngoc (Đại học Quốc gia Hà Nội, 2020)
The paper first analyzes the theoretical issues of justice, access to justice, and international standards in this field. On that basis, the author evaluates the appropriateness of the accused person’s right of access to justice provisions in Vietnam’s criminal procedure law and suggests issues to be amended and supplemented. According to the author, access to justice is both a basic human right and a means of implementation of other human rights. At the national level, although access to justice is a category contained in many disciplines of law, this term expresses the most focused and clearest in criminal procedural law, primarily through the provisions on procedural rights of accused persons. In Vietnam, the Criminal Procedure Code 2015 has several new provisions which are specialized in the 2013 Constitution’s spirit of human rights into the criminal manner and added principles related to ensuring the right for accused persons in criminal proceedings. For the first time, ‘protecting justice’ and ‘protecting human rights’ are stipulated as one of the duties of the Vietnam Criminal Procedure Code. By analyzing new regulations relating to the right of access to justice for accused persons in the Criminal Procedure Code 2015, the paper aims to answer the following questions: (1) What is the access to justice rights of accused persons in the Vietnam Criminal Procedure Code? (2) How is this right ensured through the formal institution’s framework? (3) With changes in the Vietnam Criminal Procedure Code 2015, what should Vietnam need to consider ensuring the right of access to justice for accused persons?